Constructive designing of ternary metal oxide as an anode material for high performance lithium‐ion batteries. (25th May 2021) - Jadhav, Harsharaj S.; Kim, Hern; Seo, Jeong Gil
Summary: Rational design of ternary transition metal oxides for electrochemical energy storage and conversion application is highly desirable due to their synergetic effect and structural modifications. In this regards, binder‐free urchin‐like Mn substituted NiCo2 O4 microspheres grown on conducting substrate by co‐precipitation method followed by calcination. Direct growth of active material on nickel foam (Mn0.1 Ni0.9 Co2 O4 /NF) results in a high reversible capacity of 1076 mAh/g at current density of 1.6 A/g and excellent stability of 350 cycles. As compared to bimetallic NiCo2 O4, improved electrochemical performance of Mn substituted NiCo2 O4 is mainly ascribed to the 3D structure with high surface area and abundant mesopores, which can efficiently reduce the diffusion length of ions and improve the structural stability by providing enough space for volume expansion during delithiation/lithiation processes. Abstract : Constructive designing of binder‐free ternary oxide electrode material exhibits outstanding electrochemical performance for Li‐ion battery application. The 3D structure with high surface area and enrich mesopores exhibits stability of 350 cycles with high coulombic efficiency.